2020
DOI: 10.3345/cep.2020.00010
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and childhood obesity

Abstract: Childhood obesity is a global health concern. Air pollution is also a crucial health threat, especially in developing countries. Over the past decade, a number of epidemiologic and animal studies have suggested a possible role of pre-or postnatal exposure to air pollutants on childhood obesity. Although no clear mechanism has been elucidated, physical inactivity, oxidative stress, and epigenetic modifications have been suggested as possible mechanisms by which obesity develops due to air pollution. In this rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 45 publications
4
22
0
Order By: Relevance
“…Obese individuals are uniquely susceptible to environmental exposures and it is currently unknown whether there is a higher rate of mortality from COVID-19 in obese patients that live in areas with increased air pollution. Epidemiological studies have indicated an association between obesity and air pollution ( 50 , 51 ). Studies of obese humans and animal models have demonstrated a greater decrement in pulmonary function after exposure to the criteria air pollutant ozone (O 3 ), enhanced production of proinflammatory cytokines, and markers of oxidative stress ( 52 , 53 ).…”
Section: Obese Individuals Have Increased Susceptibility To Environmementioning
confidence: 99%
“…Obese individuals are uniquely susceptible to environmental exposures and it is currently unknown whether there is a higher rate of mortality from COVID-19 in obese patients that live in areas with increased air pollution. Epidemiological studies have indicated an association between obesity and air pollution ( 50 , 51 ). Studies of obese humans and animal models have demonstrated a greater decrement in pulmonary function after exposure to the criteria air pollutant ozone (O 3 ), enhanced production of proinflammatory cytokines, and markers of oxidative stress ( 52 , 53 ).…”
Section: Obese Individuals Have Increased Susceptibility To Environmementioning
confidence: 99%
“…34 A recent review comprehensively summarized the mechanisms underlying the association between air pollution and childhood obesity. 36 We found a moderate, positive influence of harmful environmental pollutants on BMI in both genders. These findings got special importance when, according to WHO statistics, children are the main victim of secondhand smoke (in 2004, 40% of children were exposed, globally 37 ) and also, urban living increases the exposure of children to a mixture of air pollutants.…”
Section: Discussionmentioning
confidence: 58%
“…Over the past decade, a number of epidemiologic and animal studies have suggested the role of pre- and postnatal exposure to air pollutants as a cause for childhood obesity. [ 24 25 26 27 ] Although no clear mechanisms have been elucidated, physical inactivity, systemic oxidative stress, chronic activation of the hypothalamo-pituitary-adrenal axis, change in gut bacterial flora and epigenetic modifications have been suggested as possible mechanisms by which air pollution causes obesity. [ 24 ] Polyaromatic hydrocarbons which are combustion products of automobile exhausts act as endocrine-disrupting chemicals or obesogens that cause dysregulation of the hormonal network controlling appetite and endocrine tissues which changes insulin sensitivity and lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 25 26 27 ] Although no clear mechanisms have been elucidated, physical inactivity, systemic oxidative stress, chronic activation of the hypothalamo-pituitary-adrenal axis, change in gut bacterial flora and epigenetic modifications have been suggested as possible mechanisms by which air pollution causes obesity. [ 24 ] Polyaromatic hydrocarbons which are combustion products of automobile exhausts act as endocrine-disrupting chemicals or obesogens that cause dysregulation of the hormonal network controlling appetite and endocrine tissues which changes insulin sensitivity and lipid metabolism. [ 28 ] Childhood exposures to regional and traffic-related air pollutants have been shown to increase consumption of transfat and fast foods by adolescents, thereby contributing to obesogenic behavior.…”
Section: Discussionmentioning
confidence: 99%